Towards a Web Portal for Teaching and Practicing of Software Engineering Controlled Experiments - Grande, Fernando S.; Cordeiro, André F. R.; OliveiraJr, Edson (Anais da Escola Regional de Engenharia de Software (ERES); 2025: Anais da IX Escola Regional de Engenharia de SoftwareDO - 10.5753/eres.2025.16259, 2025)
Experimentation in Software Engineering is vital for improving methods and processes, but replication challenges and the lack of structured repositories limit progress. While models and ontologies organize knowledge, they do not provide integrated environments for teaching and practice. This paper presents a web portal for controlled experiments in Software Engineering, structured on a experimental process and supported by an experimentation ontology. It enables experiment registration, storage, and retrieval through a search mechanism. Tests on database connectivity, validation, and end-to-end functionality confirmed effectiveness. Future work includes enhancing usability, expanding the repository, and adding advanced analysis features.